Firm responses to the pandemic crisis: Sticky capabilites and widespread restructuring - Stefano Costa; Stefano De Santis; Giovanni Dosi; Roberto Monducci; Angelica Sbardella; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
This paper is meant to address the status of the Italian productive system in the wake of the most severe crisis economies are facing since WWII. In order to accomplish the latter task we rely on the combination of two high quality level dataset informing about so called firm behavioural traits: the first, the IMCPI (2019), collected information on organizational capabilities, practices, attitudes toward innovation, business models and strategies during the period 2016-2018, in so called usual times. The second, the SPIESC-19 (2020), was able to monitor firm responses to the pandemic crisis, collecting information in the period June - October 2020. Two results emerge out of our analysis: first, firm responses are highly pathdependent on their pre-crisis organizational capabilities; second, such crisis might turn out be more pervasive than expected, producing widespread, rather than creative, restructuring processes.
Keywords: D21; D22; D83; J24; J53; 330; Organizational capabilities; Italian productive structure; Pandemic crisis